Images of Korea I [videorecording] - Corps, Sejong Enterprises ([S.l.] The Foundation)
The new life style in Seoul are still in harmony in all, there the heritage of ancestors is preserved. Contemporary culture and original art can be seen in the Metropolis. Presents the Hanbok, a traditional customes, folk festivals and games, masked dance drama, traditional Korean wedding ceremony and the old and new buildings.
VHS.
Keywords: Korea Foundation; Sejong Enterprises Corporations; Medicine, Korean; Folk festivals -- Korea; Dance festivals -- Korea; Rites and ceremonies -- Korea; Architecture -- Korea; Buildings -- Korea; Korea -- Description and travel; Korea -- Social life and customs